Penggunaan standard metadata untuk sumber maklumat elektronik di agensi-agensi kerajaan Malaysia - Mohd Saad, Mohd Sharif; Salleh, Salmah; Abdullah Sani, Mad Khir Johari; Sahid, Noor Zaidi (Persatuan Pustakawan Malaysia, 2008)
Metadata refers to structured information that describes an information source. There are various types of metadata and metadata standards that are used by the various communities which are involved in the development of electronic information sources and systems as well as information retrieval systems. Similarly in Malaysia, various government agencies are providing digital information to the public through portals, databases and Websites. There is therefore a need to identify the use of metadata standards amongst these agencies. This paper seeks to address the need for the usage of a common metadata standard for the various agencies.